Preprints in Context - Dawson, Stephanie (Septentrio Conference Series, 2018)
Watch the VIDEO.The big story in scholarly publishing of the last years was the preprint revolution. Researchers demanded a faster channel for the early communication of their results, journal editors revised their policies to accept manuscripts also published as preprints, there was an explosion of new platforms and infrastructure, and Crossref gave the old/new species of not-really published articles a DOI. Funders even jumped into the fray, allowing researchers to use their preprints in grant proposals. The non-profit Center of Open Science launched a platform for new preprint servers, and publishers are jumping into the arena with preprint repositories like Cold Spring Harbor Laboratory Press’s bioRxiv, PeerJ Preprints, ACS’s ChemRxiv, MDPI’s Preprint.org and Elsevier’s acquisition of SSRN. These developments create new challenges for content aggregators and discovery platforms, librarians, publishers, and readers, including persistent identification of the version of record, aggregation of citations and metrics across article versions, and questions around copyright. The wide proliferation of preprint repositories across different sources also makes it difficult for researchers to reach their peers with their early results. As an aggregator and interactive discovery platform, ScienceOpen has been working to place preprints in the context of the published literature with quick preprint-filters on keyword searches and first efforts to aggregate metrics. We further provide a framework to peer review preprints in a portable system with a Crossref DOI for each peer review report, as well as editorial management of preprints in thematic collections. By showing how preprints fit in to the academic record in a broad discovery database, we are able to bring them to the attention of those searching for the newest research and more clearly highlight their status as open for peer review. Increased visibility through contextualization is our value proposition for publishers, authors and readers of preprints in 2018. We explore the disruptive potential of preprints from our experience with ScienceOpen’s discovery platform.
Keywords: Preprint; Peer Review; Metadata